The anti‐viral effect of sorafenib in hepatitis C‐related hepatocellular carcinoma. Issue 1 (24th October 2012) - Cabrera, R.; Limaye, A. R.; Horne, P.; Mills, R.; Soldevila‐Pico, C.; Clark, V.; Morelli, G.; Firpi, R.; Nelson, D. R.
Summary: Background: Sorafenib is currently the only approved systemic therapy shown to have efficacy in the treatment of advanced hepatocellular carcinoma (HCC). Recent studies suggest that hepatitis C (HCV)‐related HCC patients derive more clinical benefit from sorafenib than other subgroups, but the mechanism for this effect is unknown. In vitro data suggest that sorafenib may exert anti‐viral properties, and thus our aim in this study was to evaluate potential anti‐viral activity of sorafenib in patients with HCV‐related HCC. Aim: To evaluate potential anti‐viral activity of sorafenib in patients with HCV‐related HCC. Methods: We prospectively enrolled patients with HCV‐related HCC treated with sorafenib for up to 6 months. Baseline clinical, viral and oncologic data were collected. Patients' HCV viral loads were obtained at various time points, and compared with their baseline viral levels. No patients received any known anti‐viral therapy during this time. Results: Thirty‐three patients were identified with baseline and subsequent HCV levels available for analysis. Six patients completed 6 months of full dose sorafenib, and comparisons of their HCV viral loads showed no significant change at week 24 (difference of means = 0.3500, CI: −0.1799–0.8799, P  = 0.150), or the interim time points. Similarly, the HCV viral loads of all patients who received sorafenib and the viral loads of those patients who had tumour response to sorafenib showed no significant changes at any time point. Conclusion: Despite preclinical data and previous subgroup analyses suggesting that sorafenib has an anti‐viral effect against HCV, this study suggests that sorafenib lacks significant anti‐viral activity in HCV patients with HCC.